Growth and Spatial Dependence - The Mankiw, Romer and Weil model revisited - Cem Ertur; Thiaw Kalidou (European Regional Science Association (ERSA), 2005)
The aim of this paper is to analyze the theoretical and econometric implications of omitting spatial dependence in the Mankiw, Romer, and Weil model. Indeed, the international distribution of income levels and growth rates suggests the existence of large international disparities, and therefore the important role of location on economic performance. However, taking spatial dependence into account requires resorting to the methods of Spatial Econometrics, not only for a valid statistical inference, but also for revaluating the impact of the variables generally considered as crucial in the growth phenomenon and finding the processes underlying growth rates and income levels.
Keywords: 330